Aging and the Financing of Social Security in Switzerland - Christian Keuschnigg; Mirela Keuschnigg; Christian Jaag (Swiss Journal of Economics and Statistics, 2011)
The gains in life expectancy are expected to double the dependency ratio and increase population by 10% in Switzerland until 2050. To quantify the effects on social security and public finances, we use an overlapping generations model with five margins of labor supply: labor market participation, hours worked, job search, retirement, and on-the-job training. A passive fiscal strategy would be very costly. A comprehensive reform, including an increase in the retirement age to 68 years, may limit the tax increases to 4 percentage points of value added tax and reduce the decline of per capita income to less than 6%.
Keywords: D58; D91; H55; J26; J64; 330; Aging; social security; retirement; human capital; unemployment